2018
DOI: 10.1002/2017jd027729
|View full text |Cite
|
Sign up to set email alerts
|

Initial Breakdown Pulse Parameters in Intracloud and Cloud‐to‐Ground Lightning Flashes

Abstract: This study analyzes the largest initial breakdown (IB) pulse in flashes from four storms in Florida; data from three sensor arrays are used. The range‐normalized, zero‐to‐peak amplitude of the largest IB pulse was determined along with its altitude, duration, and timing within each flash. Appropriate data were available for 40 intracloud (IC) and 32 cloud‐to‐ground (CG) flashes. Histograms of amplitude of the largest IB pulse by flash type were similar, with mean (median) values of 1.49 (1.05) V/m for IC flash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 37 publications
5
20
0
Order By: Relevance
“…Among the 20 CG flashes we found that the IB pulse with the largest amplitude occurred on average 0.5 ms after the first recognizable IB pulse; this value is in good agreement with an average of 0.6 ms for 32 CG flashes in Florida determined by Smith et al (). In these same flashes the most energetic VHF pulse was found on average 1 ms after the first recognizable IB pulse.…”
Section: Analysis Of Waveformssupporting
confidence: 90%
“…Among the 20 CG flashes we found that the IB pulse with the largest amplitude occurred on average 0.5 ms after the first recognizable IB pulse; this value is in good agreement with an average of 0.6 ms for 32 CG flashes in Florida determined by Smith et al (). In these same flashes the most energetic VHF pulse was found on average 1 ms after the first recognizable IB pulse.…”
Section: Analysis Of Waveformssupporting
confidence: 90%
“…This approach makes it possible to explain short IEC times followed by powerful IBPs. Furthermore, because of the hypothesis of small‐scale 3‐D variations in E , the Mechanism also readily explains the varied development of initiation events in different flashes, including the wide range of IEC durations and amplitudes (e.g., Marshall, Schulz, et al, 2014), the wide range of IBP durations, inter‐IBP times, IBP amplitudes, number of subpulses in the classic IBPs (e.g., Bandara et al, 2019; Marshall et al, 2013; Stolzenburg et al, 2013, 2014), and the seemingly random amplitude order of the classic IBPs (e.g., Smith et al, 2018). These variations among real lightning flashes are much harder to understand if initiation occurs a single smooth region of large E .…”
Section: Discussionmentioning
confidence: 99%
“…For each subsequent IB pulse the field enhancement at the ends of the growing initial leader, combined with the statistically distributed, 3‐D groups of nascent plasma networks, strongly influences the linear trajectory of the initial leader, thereby accounting for changes in initial leader direction (Stolzenburg et al, 2013) and for initial leader branches (Stolzenburg et al, 2014, 2020). It is well known that the series of IBPs is very different from one flash to another, including a seemingly random order of IBP FA amplitudes, IBP durations, and time between successive IBPs as shown by comparing Figures 11 and 12 below (see also Figures 4 and 5 in Bandara et al, 2019; and Figures 3–5 in Smith et al, 2018). However, the Mechanism proposed can account for these variations; indeed, a turbulent distribution of charges and ignition of positive streamers by an EAS‐RREA essentially requires such variations.…”
Section: The Mechanismmentioning
confidence: 97%
See 1 more Smart Citation
“…Each of the IBPs chosen “was one of the largest … in the IB stage” of the flash (Karunarathne et al, ). Based on their E ‐change amplitudes of 3–8 V/m range normalized to 100 km, these IBPs had amplitudes that were much larger than the mean (median) values of −1.35 (−0.87) V/m for the largest IBP in CG lightning flashes (Smith et al, ).…”
Section: Resultsmentioning
confidence: 99%